Analisis Going Concern Pada Pelaku Usaha Nelayan Di Kecamatan Nusaniwe Kota Ambon - Paskanova Christi Gainau; Trisye Natalia Kilay; Ribka S. F. Bonara (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2023)
One of sectors massively contributing in the economy of Ambon city is fishery and marine. However, fishermen as one of the business actors who run this business are still on the poverty line even though they operate business every day. This study aims to analyze the going concern aspects applied by business actors so far. A qualitative approach with source triangulation techniques was used where researchers conducted in-depth interviews and observations to business actors in Dusun Eri, Latuhalat Village, and Seri Village. The results found that the going concern aspects that have been applied tend to adopt traditional methods that have been going on since ancient times, such as only focusing on selling fresh fish as their product characteristic so business actors are reluctant to innovate. The obstacles are the lack of self-motivation and government capital support, as well as the low understanding of technology. In addition, the going concern aspect of this business is also not determined by the accounting process because all business actors do not carry out accounting processes in their business. The financial management process that has been carried out by business actors is limited to allocating sales proceeds for business operations, family economic needs, and personal savings. This allocation process is not recorded in a specific book and only relies on their intuition and verbal calculations.